Management of Cocoa Plant Pests & Diseases in East Luwu Regency - Nurhikmah Mutmainna Sari; Abdul Munif; Widodo; Agus Purwantara (Jurnal Ilmu Pertanian Indonesia, 2025)
East Luwu Regency is one of South Sulawesi's regencies with potential in the plantation sector, especially cocoa plants, with a production of 12,250 tons/year. Cocoa productivity has yet to be achieved optimally due to the lack of care and maintenance carried out by farmers, which increases the intensity of pest & disease attacks. This study evaluates farmers' knowledge, attitudes, and actions in managing cocoa plants and plant pathogens in East Luwu Regency. This study was conducted through direct interviews using a structured questionnaire sent to 50 farmers in Burau and Wotu Districts, East Luwu Regency. Respondents were selected purposively, considering that they were easy to find and the location of the plantation was easy to reach. Data are presented in tabular, graphical, and descriptive forms in Microsoft Excel to explain the relationship between farmers' knowledge, attitudes, and actions in managing cocoa VSD disease. The results showed that most of the respondent were active farmer groups. Pests & diseases are problems farmers face in cocoa cultivation. Most farmers used the MCC 02 clone, and the planting distance was 3´3 m. The diseases most commonly found in farmers' cocoa fields include VSD, fruit rot, upas fungus, and stem cancer. Pest & disease control was done through chemical pesticides and pruning (cultivation techniques). Cocoa farmers in Burau and Wotu Districts routinely carry out pruning to control disease in cocoa fields. Farmers prune cocoa plants to remove diseased branches and stimulate the growth of flowers and fruit. Keywords: action, attitude, knowledge, questionnaire